3 RENAISSANCE IN UZBEKISTAN - Kirillova. L. D. (Scholar Express Journal, 2022)
The article is based on the analysis of historical sources, according to which spirituality and enlightenment of the peoples of the Turanian land in the IXXII and XII-XIV centuries were the period of the Eastern 1-2-Renaissance and were recognized by the whole world. Also, analytical data on the positive works of great thinkers and scientists who lived in the East and left us a rich scientific and spiritual heritage, such as Abu Ali ibn Sino, Al-Khorezmi, Abu Rayhan Beruni, Amir Temur, in the fields of science, culture, and enlightenment, are historical facts, as well as the work carried out in Uzbekistan in the field of science, culture, and education is recognized as the beginning of the stage of the third Renaissance
Keywords: Culture; education; scientific and universal spirituality; new civilizations.